Lambda point thermodynamics of confined liquid helium: negative surface specific heat - Ferrell, R. A.; Bhattacharjee, J. K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
We present some theoretical considerations that are relevant to the forthcoming measurements in microgravity of the specific heat of confined liquid helium (the flight experiment &quotCHEX&quot). Primary attention is devoted to the suppression near the boundaries, the &quotnegative surface specific heat&quot. Above the lambda point, we compute this to lowest order in the epsilon-expansion: below the lambda point our discussion is more restricted.